The effect of compressive force combined with mechanical vibration on human alveolar bone osteoblasts - Chatchai Chatmahamongkol; Anute Pravitharangul; Srisurang Suttapreyasri; Chidchanok Leethanakul (Elsevier, 2019)
Objective: This study aimed to investigate the effects of compressive force combined with mechanical vibration on the expression of pro-inflammatory cytokines that promote osteoclastogenesis and related to orthodontic tooth movement acceleration in human alveolar bone osteoblasts in vitro. Methods: Osteoblasts were subjected to compressive force (C), mechanical vibration (V), compressive force combined with mechanical vibration (CV), or no force as a control for 12, 24 and 48 h. Interleukin-1 beta (IL-1β), interleukin-6 (IL-6), receptor activator of nuclear factor kappa-Β ligand (RANKL) and osteoprotegerin (OPG) mRNA and protein expression were assessed using quantitative real-time polymerase chain reaction and enzyme-linked immunosorbent assays. Results: In C and CV groups, IL-1β and IL-6 mRNA and protein expression were significantly higher and OPG mRNA and protein expression were significantly lower than control and V groups. However, the expressions were not different between C and CV groups. RANKL mRNA and protein expression were not different between any groups. While, OPG mRNA and protein expression in V group were significantly higher than control group. Conclusions: Vibration neither enhanced nor inhibited the expression of IL-1β, IL-6, RANKL and OPG in compressed human alveolar bone osteoblasts.